2007
DOI: 10.1259/bjr/61246651
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic findings of small bowel intussusception, focusing on differentiation from ileocolic intussusception

Abstract: The purpose of this study was to evaluate the typical ultrasonographic findings of transient small bowel intussusception (SBI) and to differentiate it from ileocolic intussusception (ICI) in paediatrics. 22 transient SBI (male:female = 13:9, age: 7-132 months (mean 38 months)) and 27 ICI (male:female = 19:8, age: 1-60 months (mean 13 months)) patients diagnosed on ultrasonography were retrospectively evaluated. The findings of location, diameter, thickness of outer rim, and inclusion of mesenteric lymph nodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
4
24
0
2
Order By: Relevance
“…1,17,18 Characteristic US findings of the transient small bowel "ileal-ileal" intussusception include small size of the doughnut ring (2-3 cm), no recognizable lead point, short segment length of less than 3.5 cm, normal vascularity on color Doppler US, and preserved wall motion. 1,4,13,16,17,[19][20][21] Due to the availability of US imaging in most emergency departments, small bowel intussusceptions may be readily identified and characterized by these recommended criteria.…”
Section: Discussionmentioning
confidence: 99%
“…1,17,18 Characteristic US findings of the transient small bowel "ileal-ileal" intussusception include small size of the doughnut ring (2-3 cm), no recognizable lead point, short segment length of less than 3.5 cm, normal vascularity on color Doppler US, and preserved wall motion. 1,4,13,16,17,[19][20][21] Due to the availability of US imaging in most emergency departments, small bowel intussusceptions may be readily identified and characterized by these recommended criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of most SBIs relies on ultrasound scanning, and types of intussusceptions can be readily distinguished [5,6,10]. In addition, with the development and wide application of ultrasound technology, the presence of temporary or transient small bowel intussusceptions has become clinically apparent [1,4,5,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the development and wide application of ultrasound technology, the presence of temporary or transient small bowel intussusceptions has become clinically apparent [1,4,5,8,11]. Doi et al [8] have suggested the term benign small bowel intussusception to describe those that are found incidentally and/or resolve spontaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review noted that larger intussusception diameter and the presence of lymph nodes within the intussusception favored ileocolic intussusception [28] . In one review, mean AP diameter of ileocolic intussusception was 2.53 cm compared to 1.38 cm of small bowel intussusception [29] . Small bowel intussusceptions have very little fat centrally and occur in older children with bowel disorders such as HenochSchonlein Purpura, Crohn disease, and celiac sprue; they are also seen in post-operative patients and in patients with small bowel mass acting as a lead point.…”
Section: Acquired Disordersmentioning
confidence: 99%